14-3-3 proteins: a family of versatile molecular regulators - Obšilová, Veronika; Šilhán, Jan; Bouřa, Evžen; Teisinger, Jan; Obšil, Tomáš (Physiological research, 2008)
The 14-3-3 proteins are a family of acidic regulatory molecules found in all eukaryotes. 14-3-3 proteins function as molecular scaffolds by modulating the conformation of their binding partners. Through the functional modulation of a wide range of binding partners, 14-3-3 proteins are involved in many processes, including cell cycle regulation, metabolism control, apoptosis, and control of gene transcription. This minireview includes a short overview of 14-3-3 proteins and then focuses on their role in the regulation of two important binding partners: FOXO forkhead transcription factors and an enzyme tyrosine hydroxylase.
Keywords: 14-3-3 Proteins; konzervovaná sekvence; tyrosin-3-monooxygenasa; Models, Molecular; Protein Binding; Protein Structure, Quaternary; Tyrosine 3-Monooxygenase; molekulární sekvence - údaje; kvarterní struktura proteinů; molekulární modely; Protein Conformation; vazba proteinů; Protein Isoforms; Forkhead Transcription Factors; protein - isoformy; lidé; proteiny 14-3-3; Amino Acid Sequence; zvířata; Humans; Molecular Sequence Data; forkhead transkripční faktory; Conserved Sequence; konformace proteinů; Animals; sekvence aminokyselin